2010
DOI: 10.1073/pnas.1001513107
|View full text |Cite
|
Sign up to set email alerts
|

Common biosynthetic origins for polycyclic tetramate macrolactams from phylogenetically diverse bacteria

Abstract: A combination of small molecule chemistry, biosynthetic analysis, and genome mining has revealed the unexpected conservation of polycyclic tetramate macrolactam biosynthetic loci in diverse bacteria. Initially our chemical analysis of a Streptomyces strain associated with the southern pine beetle led to the discovery of frontalamides A and B, two previously undescribed members of this antibiotic family. Genome analyses and genetic manipulation of the producing organism led to the identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
270
0
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(289 citation statements)
references
References 38 publications
7
270
0
10
Order By: Relevance
“…Comparison of the eight strains included in this group revealed that they grouped within one of the three clades of Streptomyces spp. that were identified by Hulcr et al 30 This clade also included a strain isolated from the pine-infesting beetle D. frontalis 13,28 and cellulose degrading Streptomyces spp. associated with a pineinfesting siricid wasp, Sirex noctilio 30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparison of the eight strains included in this group revealed that they grouped within one of the three clades of Streptomyces spp. that were identified by Hulcr et al 30 This clade also included a strain isolated from the pine-infesting beetle D. frontalis 13,28 and cellulose degrading Streptomyces spp. associated with a pineinfesting siricid wasp, Sirex noctilio 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…The clade formed by our isolates and those from S. noctilio and D. frontalis was identified in another study. 32 Several previously reported isolates from pine-infesting insects 13,28,30,31 were grouped into two clades, based on their core genomes. One of these clades, containing a single isolate from both S. noctilio 31 and D. ponderosae had remarkable lignocellulose digestion capacity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SPB78 isolated from same beetle ( Figure 5). 26 Similar symbiotic systems associated with social bees have scarcely been investigated yet. Pioneer studies in Brazil have recently reported that the Brazilian social stingless bee Scaptotrigona depilis cultivate a fungus to survive.…”
Section: Other Insect-microbial Symbiosesmentioning
confidence: 99%